The Impact of Interplay Between Intrinsic Capabilities, Extrinsic Support, and System Quality on e-Learning Service Experiences - Mohammad Shuaib Mir; Golooba Moses; Yonis Gulzar; Faheem Ahmad Reegu (IEEE Access)
Despite the numerous benefits of e-learning, overall the acceptance, effectiveness, and success of e-learning projects still vary significantly. Although several studies have investigated the factors that affecting e-learning, most of the studies have largely overlooked the impact of individual e-learners’ intrinsic capabilities on e-learning service experiences. Yet, given that e-learning is largely an independent, student-centered learning strategy, its success largely depends on the learner’s intrinsic capabilities and the extrinsic support they receive from their peers and online community. The aim of this study therefore, was to empirically examine the impact of the interplay between system quality, extrinsic support, and intrinsic capabilities on e-learning experiences. This study employed a quantitative research strategy, using a survey instrument to collect quantitative data from 381 postgraduate students at selected Malaysian universities. Overall, the results reveal a very strong impact of individual intrinsic capabilities on e-learning service experiences. Specifically, the findings indicate that higher levels of intrinsic capabilities in terms of technology self-efficacy correlate with lower anxiety and increased self-esteem among e-learners. Whereas strong locus of control enables learners to self-regulate, manage study time effectively, and navigate deadlines proficiently ultimately leading to better e-learning service experiences. The combined impact of the interplay between extrinsic support and intrinsic capabilities was also found to have a significant positive impact on e-learning service experiences. Generally, this study underscores the critical role of e-learners in co-creating their learning experiences through peer-to-peer learning and highlights the importance of intrinsic capabilities in fostering control, self-esteem, and motivation. The findings suggest that e-learning platforms should promote discussions, group projects, and collaborative problem-solving activities to build a sense of community, support, motivation, and shared learning goals among e-learners, ultimately enhancing service experiences.